AN AUTOETHNOGRAPHIC APPROACH TO IDENTITY EDUCATION AMONGST CROSS-CULTURE KIDS IN LITHUANIAN SCHOOLS - Chu, Ling Yi (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
While Lithuanian schools face an influx of repatriated pupils post-Brexit and due to the COVID 19 pandemic, there is still no clear framework to support schools in integrating the increasing Cross Culture Kids (CCKs) and its school community and beyond. This paper examines the application of autoethnography as a pedagogical strategy for school agents to foster identity narrative spaces in classrooms and as a research method for investigating identity formation in educational contexts nurturing cross-cultural competencies in Lithuanian classrooms. This piece is part of the preparation work conducted for the upcoming serial cultural dialogue workshops with CCKs between 15-18, which borrows from the TARMAC ‘multicultural story’ framework (Ward and Keck, 2021). While autoethnography engages individuals in cultural-analysis-style interpretations of self-reflection, this process importantly aids the location of selves in one’s own narratives by exploring the self-other, personal-political, and self-society didactic- for all the stakeholders in the dialogue- such as the workshop facilitators/researchers and the CCKs and its non-CCK counterparts. This leads to the implications of philosophical and practical education approaches exploring identity and intercultural communication in alternative and non-traditional forms (Wall, 2006). Overall, this paper contributes to the formation of cross-culture transitional care awareness and strategies implemented in Lithuanian schools.